Facilitating conceptual change in students' understanding of concepts related to pressure - Ozkan, Gulbin; Selcuk, Gamze Sezgin (IOP PUBLISHING LTD, 2016)
The aim of this research was to explore the effects of three different types of methods of learning physics (conceptual change-based, real life context-based and traditional learning) on high school physics students in the 11th grade in terms of conceptual change they achieved in learning about the various topics (pressure exerted by solids, pressure in stagnant liquids and gases, buoyancy, Bernoulli's principle). In this study, a pre-test/post-test quasi-experimental method with nonequivalent control group, involving a 3 (group) x 2 (time) factorial design was used. Study group 1 were given the conceptual change texts on the mentioned subjects, study group 2 were offered a teaching approach based on real life context-based learning, whereas the control group was taught in the traditional style. Data for the research were collected with the 'pressure conceptual test'. As a result of research, the number of misconceptions had been reduced or shifted altogether in all three groups. After the instruction, it was seen that none of the students formed new misconceptions. It was found that the most positive change could be seen in the conceptual change text group followed by context-based and lastly traditional. The fact that none of the students formed new misconceptions is important, particularly since research such as the following shows that conceptual change is tenuous and inconsistent, taking time to shift in a sustained manner.
Keywords: conceptual change texts; conceptual change; real life context-based learning; pressure; TEXT STRUCTURE; SCIENCE; PHYSICS; MISCONCEPTIONS; ELECTRICITY; ENERGY; Education & Educational Research